(3MjGI GdMjhGf GdcHQis - (3eMeO Hf ehSi Hf YjSi Hf Ydj GdOejQj, CHh GdHbGA, ceGd GdOjf , (B808 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj TQa fhY GdEfSGfhHYO agPG cJGH de jSCdfj CMO JUfjaghJHjf GdMce aj GdQgGf SGHb GdNjdaGSJNQJ Gddgaj hVY cJGH aj gPG GdTCf hSejJg MjGI GdMjhGfs
(3BNQgG (B:s
(3SajfI ef CcGHQ GdeMOKjf dCfg cGf EPG XaQ HeMOK SeYejY eG YfOg hcJHg MJi dG jHbi YfOg TjAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 118s
(3eYLe GdeDdajf(B: 3 / 743s
(3cTa GdXfhf(B: 1 / 696s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdcjejGA hGdWHjYjGJs